Perfil de ácidos graxos do leite, textura da manteiga e comportamento ingestivo de vacas da raça holandesa alimentadas com grãos de girassol peletizado com ou sem lignosulfonato - Figueiroa, Fábio José Ferreira (2010)
The experiment was conducted at the Experimental Farm of (FEl), of the State University of Maringá (UEM) with the purpose of evaluating the effect of lignosulphonate addition and pelietization of ground sunflower seed on the profile of miik fatty acids, butter texture and ingestion behavior of the animals. Four multiparous Holstein cows with average weight of 568 ± 75.02 kg, 23.17 ± 4.73 kg of milk per day and 130 ± 28.08 days in milking were used. The animals were housed in individual pens and assigned to four treatments: concentrate with ground sunflower seed (GM), concentrate with ground sunflower seed and 5% lignosulphonate (GML), pelletized concentrate with ground sunflower seed (GMP) and pelletized concentrate and 5% lignosulphonate with grounci sunflower seed (GMPL). Each experimental period comprehended 21 days, 14 days of adaptation and seven days for data collection. The forage:concentrate ratio was 60:40, and the forage composed of com silage. The experimental diets were formulated to be isonitrogenous and isoenergetic. Immediately after milking the production of each individual cow was recorded. For analysis of protein, fat, lactose, total solids, urea nitrogen, somatic cell count (SCC) in milk and milk fatty acid profile, milk samples were collected from each cow at the first and second experimental day. Additionally, milk samples were collected for butter. For analysis of blood parameters, blood samples were collected via tail on the last day of each experimental period. On the last day of each experimental period, visual assessments of behavior were performed every five minutes for 24 hours, and the local climatic data were collected. Milk production and milk yield corrected for 4% fat were similar among treatments (P>0.05). However, the fat content of milk was lower (P<0.05) in the pelletized treatments when compared to the others. The other evaluated miIk components, and the concentration of. N-urea and somatic cell count were not influenced by the treatments. The milk fatty acid profile suffered a slight change in the levels of 16:1 n-11 and trans 18:1 n-9, which were higher for pelletized treatments. The levels of glucose, triglycerides, total cholesterol, HDL, LDL and VLDL in blood plasma were not affected by the treatments (P> 0.05), as well as the firmness and adhesiveness of butter. The variabies of standing and eating (PC), standing and ruminating (PR), standing and drinking water (PB), standing at rest (P0), Iying ruminating (DR) and lying at rest (DO) were similar between treatinents, with no significant difference by Tukey test at 5% probability. In conclusion, the addition of lignosulphonate in the diet of dairy cows is not effective in protecting sunflower fatty acids against ruminal biohydrogenation. The process of pelietizing the sunflower-based diets significantly decreases the milk fat content.